Circadian rhythms in heart rate, motility, and body temperature of wild‐type C57 and eNOS knock‐out mice under light‐dark, free‐run, and after time zone transition - Arraj, Mahran; Lemmer, Björn (Chronobiology international, 2006)
The nitric oxide (NO) system is involved in the regulation of the cardiovascular system in controlling central and peripheral vascular tone and cardiac functions. It was the aim of this study to investigate in wild‐type C57BL/6 and endothelial nitric oxide synthase (eNOS) knock‐out mice (eNOS‐/‐) the contribution of NO on the circadian rhythms in heart rate (HR), motility (motor activity [MA]), and body temperature (BT) under various environmental conditions. Experiments were performed in 12∶12 h of a light:dark cycle (LD), under free‐run in total darkness (DD), and after a phase delay shift of the LD cycle by −6 h (i.e., under simulation of a westward time zone transition). All parameters were monitored by radiotelemetry in freely moving mice. In LD, no significant differences in the rhythms of HR and MA were observed between the two strains of mice. BT, however, was significantly lower during the light phase in eNOS‐/‐ mice, resulting in a significantly greater amplitude. The period of the free‐running rhythm in DD was slightly shorter for all variables, though not significant. In general, rhythmicity was greater in eNOS‐/‐ than in C57 mice both in LD and DD. After a delay shift of the LD cycle, HR and BT were resynchronized to the new LD schedule within 5-6 days, and resynchronization of MA occurred within 2-3 days. The results in telemetrically instrumented mice show that complete knock‐out of the endothelial NO system—though expressed in the suprachiasmatic nuclei and in peripheral tissues—did not affect the circadian organization of heart rate and motility. The circadian regulation of the body temperature was slightly affected in eNOS‐/‐ mice.